Laboratory jargon and misconceptions in Chemistry – an empirical study - Hans-Dieter Barke; Joline Büchter (Universitas Pendidikan Indonesia (UPI), 2023)
Lecturers mostly use “laboratory jargon” in their seminars and the question comes up whether teacher students are taking this jargon for their terminology, developing “school-made misconceptions”, or even transferring them later into Chemistry instruction. One example: “2 hydrogens react with 1 oxygen to form 2 water”, is often heard – instead of pointing out that 2 H2 molecules and 1 O2 molecule are forming 2 H2O molecules. This last statement is totally clear and the learner will develop applicable mental models. An empirical pilot study showed the first results. About half of the investigated participants could reflect on and correct given jargon statements – but even after three years of studying Chemistry, the other students are staying with that jargon or other alternative conceptions.